Resiniferatoxin and Tetrodotoxin Induced NPY and TH Immunoreactivity Changes Within the Paracervical Ganglion Neurons Supplying the Urinary Bladder - Burliński, Piotr J. (Humana Press Inc, 2012)
Both resiniferatoxin (RTX) and tetrodotoxin (TTX) have been reported to be effective in several urinary bladder dysfunction clinical trials. The aim of this study was to establish the effect of intravesical administration of RTX and TTX on neuropeptides Y (NPY) and tyrosine hydroxylase (TH) relationship in the paracervical ganglion (PCG) neurons supplying the urinary bladder in the pig. TH is an enzyme responsible for catalyzing the conversion of the amino acid L-tyrosine to dihydroxyphenylalanine (DOPA) and is used as a marker of catecholaminergic neurons. NPY augments the vasoconstrictor effects of noradrenergic neurons, and is involved in pathophysiological processes as a neuromodulator. To identify the PCG neurons supplying urinary bladder Fast Blue (FB) was injected into the bladder wall prior to intravesical RTX or TTX administration. Consequent application of immunocytochemical methods revealed that in control group 64.08 % of FB-positive PCG neurons contain NPY and 4.25 % TH. Intravesical infusion of RTX resulted upregulation of the NPY-IR neurons to 82.97 % and TH-IR to 43.78 %. Also administration of TTX induced further increase number of TH-IR neurons to 77.49 % but induced decrease number of NPY-IR neurons to 57.45 %. Both neurotoxins affect chemical coding of the PCG neural somata supplying urinary bladder, but the effects of their action are different. This results shed light on possible involvement of RTX and TTX on curing tissue, and potentially could help us to broaden our neurourological armamentarium.